2021
DOI: 10.1126/sciadv.abj5363
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of SbmA, a promiscuous transporter exploited by antimicrobial peptides

Abstract: Antibiotic metabolites and antimicrobial peptides mediate competition between bacterial species. Many of them hijack inner and outer membrane proteins to enter cells. Sensitivity of enteric bacteria to multiple peptide antibiotics is controlled by the single inner membrane protein SbmA. To establish the molecular mechanism of peptide transport by SbmA and related BacA, we determined their cryo-electron microscopy structures at 3.2 and 6 Å local resolution, respectively. The structures show a previously unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 54 publications
(62 reference statements)
1
49
0
Order By: Relevance
“…The expression of BacA Sm and all its tested homologs (SbmA, BacA Ba , BclA) reverted the PHZ-susceptible phenotype in PHZ-resistant double mutants, which is consistent with the promiscuous peptide uptake by these transporters [10][11][12][13][14]25,28]. While there is no in vitro system to study transport by YejABEF, we have previously developed a system to monitor P a g e | 11 of 36 substrate transport by SLiPTs including BacA Sm and SbmA Ec [10]. We used this liposome transport assay to provide direct evidence of the ability of BacA Sm to internalize PHZ.…”
Section: In Vitro Transport Assay Shows the Internalization Of Phz Vi...supporting
confidence: 74%
“…The expression of BacA Sm and all its tested homologs (SbmA, BacA Ba , BclA) reverted the PHZ-susceptible phenotype in PHZ-resistant double mutants, which is consistent with the promiscuous peptide uptake by these transporters [10][11][12][13][14]25,28]. While there is no in vitro system to study transport by YejABEF, we have previously developed a system to monitor P a g e | 11 of 36 substrate transport by SLiPTs including BacA Sm and SbmA Ec [10]. We used this liposome transport assay to provide direct evidence of the ability of BacA Sm to internalize PHZ.…”
Section: In Vitro Transport Assay Shows the Internalization Of Phz Vi...supporting
confidence: 74%
“…Pyranine has been used to monitor the proton-pumping activity of different types of rhodopsins: sensory rhodopsin-I and II [129,130], xR [131], ChR [132], aR [133], pR [134], and xanthorhodopsin [135,136]. Recently, Ghilarov et al revealed the molecular mechanism of the membrane protein SbmA [137]. The proton-pumping activity of the protein reconstituted into liposomes was measured by pyranine fluorescence.…”
Section: Membrane-impermeable Dye-based Assaysmentioning
confidence: 99%
“…In the case of E. coli SbmA-mediated transport of microcin J25, it is thought that SbmA makes specific contacts with the peptide and is powered by a proton gradient (Ghilarov et al, 2021). Unlike SbmA, which possesses the transmembrane but not nucleotide-binding domain of ABC transporters (Ghilarov et al, 2021; Runti et al, 2013), B. cepacia YddA is predicted to have a C-terminal ATP-binding domain. As such, YddA may use a transport mechanism distinct from SbmA, another intriguing question for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although SbmA homologs have been repeatedly associated with lasso peptide transport, how they interact with their cargo is poorly understood. In the case of E. coli SbmA-mediated transport of microcin J25, it is thought that SbmA makes specific contacts with the peptide and is powered by a proton gradient (Ghilarov et al, 2021). Unlike SbmA, which possesses the transmembrane but not nucleotide-binding domain of ABC transporters (Ghilarov et al, 2021; Runti et al, 2013), B. cepacia YddA is predicted to have a C-terminal ATP-binding domain.…”
Section: Discussionmentioning
confidence: 99%